Adding color contrast to black and white medical images - Foo, En Zhao (2019)
The purpose of this project is to analyze optical signals of medical images obtained using optical coherence tomography. Based on the biophysical linkages between the biological components and specific optical signal, nature or artificial color will be added to the black and white images to facilitate better visualization and improved diagnosis of diseases. This project involves signal analysis and application of the standard diagnostic procedures to determine the stage of diseases.